Recent developments and new directions in soft computing - Abbasov, Ali M.; Yager, Ronald R.; Shahbazova, Shahnaz N.; Reformat, Marek Z.; Zadeh, Lotfi A. (Studies in Fuzziness and Soft Computing, 2014)
The book reports on the latest advances and challenges of soft computing. It  gathers original scientific contributions written by top scientists in the field and covering theories, methods and applications in a number of research areas related to soft-computing, such as decision-making, probabilistic reasoning, image processing, control, neural networks and data analysis.